1978
DOI: 10.1016/0022-0248(78)90155-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography of aligned Fe-Al eutectoid

Abstract: By applying the Weissenberg technique to small pieces of duplex crystals of FeA1 and FeA12, produced by directional eutectoid decomposition, it has been found possible not only to establish the previously unknown unit cell parameters of FeA12, but also the orientation relationship between FeA1 and FeA12. The unit cell of FeAI 2 can be described as an A-centred pseudo-monoclinic cell with a = 7.594, b = 16.886, c = 4.863 A, a = 89.55 ° ,/3 = 122.62 ° and 7 = 90-43°. The orientation relationship between both pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…In the present study, the orientation relationship, as determined previously by Bastin et al (1978) and Hirata et al (2008), will be confirmed and the supposed differences will be examined. In addition, the interface of the FeAl and FeAl 2 lamellae is investigated by means of local orientation determination and cross sectioning.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the present study, the orientation relationship, as determined previously by Bastin et al (1978) and Hirata et al (2008), will be confirmed and the supposed differences will be examined. In addition, the interface of the FeAl and FeAl 2 lamellae is investigated by means of local orientation determination and cross sectioning.…”
Section: Introductionsupporting
confidence: 62%
“…In addition, the interface of the FeAl and FeAl 2 lamellae is investigated by means of local orientation determination and cross sectioning. In contrast to the investigation of Bastin et al (1978), a distinct preferential interface can be identified. By applying the experimental data, the atomistic details of the relationship of the involved crystal structures are discussed.…”
Section: Introductionmentioning
confidence: 79%
“…In the second sample, apart from the Al 2 Fe, also Table 4 together with these obtained in Ref. [36,37] and the observed differences are lower than 1%. In the following step, the obtained phases were cut into small pieces suitable for using in the calorimeter.…”
Section: Resultssupporting
confidence: 37%
“…This is not surprising as the eutectoid formation/decomposition occurs as a spontaneous process not allowing long-range diffusion processes but only short-range rearrangements of the atoms. In addition it is well-known from the literature that there exist simple orientation relationships in the aligned lamellar microstructures between the phases FeAl and FeAl 2 [28].…”
Section: Relation To the B2 Feal Structure -Interatomic Distancesmentioning
confidence: 98%